2018
DOI: 10.18280/ijht.360107
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic evolution model and experimental study of gas permeability under multiple factors

Abstract: This paper aims to ascertain the relationship between permeability and temperature of gasfilled coal. For this purpose, the author probed into various influencing factors of permeability, and constructed a permeability evolution model involving temperature, effective stress, gas pressure and humidity. Then, the proposed model was improved through an experimental research using thermal-fluid-solid coupling triaxial seepage test device. It is found that the theoretical results of the model agree well with the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Published studies show that the reaction of the crack of oxygen-containing functional group is main form at the early stage. With coal rank increasing, the reaction turns to aromatics branched chain cracking, then to bituminous larger molecules crack during the stage of the coal-generated hydrocarbon process [19][20][21][22][23].…”
Section: Relationship Between Adsorption Capacity and Coal Crystallitementioning
confidence: 99%
“…Published studies show that the reaction of the crack of oxygen-containing functional group is main form at the early stage. With coal rank increasing, the reaction turns to aromatics branched chain cracking, then to bituminous larger molecules crack during the stage of the coal-generated hydrocarbon process [19][20][21][22][23].…”
Section: Relationship Between Adsorption Capacity and Coal Crystallitementioning
confidence: 99%
“…It was found that the change of coal permeability with temperature variation primarily depended on the interaction of thermal and effective stresses, and was related to coal deformation. In addition, some permeability formulas combined with temperature and effective stress were successfully proposed to predict coal permeability under different conditions [30][31][32]. Heat injections increased coal permeability because in coal, sharp temperature change possibly leads to uneven thermal deformation and microcrack generation [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%